Risco para diabetes mellitus tipo 2 em usuários atendidos em unidades de saúde da família - Lima , Carla Lidiane Jácome de (2017)
Introduction: Stress, consumerism, alcohol, smoking, sedentary lifestyle, excessive caloric intake and lack of physical activity are some of the possible risk factors capable of triggering diseases, among them diabetes mellitus (DM). Type 2 DM is characterized by defects in the action or secretion of insulin, manifesting mainly in overweight people, obese and with hereditary factors. Objective: To evaluate the risk of developing type II diabetes mellitus in patients treated at the Family Health Units of the city of João Pessoa-Paraíba. Method: This is a cross-sectional study of a quantitative approach conducted with 266 patients of basic health care in 21 health units of the Health District III, located in the capital state João Pessoa-PB, between April and June 2016. For the collection of data two instruments were used: the first containing sociodemographic variables and individual characteristics; the second refers to the FINDRISC (Finnish Diabetes Risk Score). For the analysis of the data there were used descriptive statistics and inferential analysis techniques considering a level of significance of 95%; and for comparison of the associated characteristics, inferential statistics were used, with the calculation of gross prevalence ratios with confidence interval of 95%. This project was approved by the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraíba-UFPB, CAEE 52727916.3.0000.5188. Results: Data showed that, of the 266 interviewed users, 83.1% were women, 59.4% were under 45 years of age, 42% had completed high school, 51% declared themselves to be maroon, 57% represented the monthly income from 1 to 3 minimum wages, 36.4% the time at the BHU from 1 to 5 years. Regarding individual characteristics, 24% were hypertensive, 9.8% were smokers and 21.5% were alcoholics. With regard to risk, the study participants presented a slightly high risk of 31.2%, followed by a high risk of 27.1% and a very high risk of 1.5%. Conclusion: There are several risk factors for the development of T2DM identified in the study participants, most of which are changeable, thus justifying the importance of screening as a preventive action in order to help health professionals to act on these at-risk users which can lead to delay the development of the disease.